Land‐use change erodes trophic redundancy in tropical forest streams: Evidence from amino acid stable isotope analysis. Issue 6 (19th March 2021) - Chua, Kenny W. J.; Liew, Jia Huan; Wilkinson, Clare L.; Ahmad, Amirrudin B.; Tan, Heok Hui; Yeo, Darren C. J.
Abstract: Studies have shown that food chain length is governed by interactions between species richness, ecosystem size and resource availability. While redundant trophic links may buffer impacts of species loss on food chain length, higher extinction risks associated with predators may result in bottom‐heavy food webs with shorter food chains. The lack of consensus in earlier empirical studies relating species richness and food chain length reflects the need to account robustly for the factors described above. In response to this, we conducted an empirical study to elucidate impacts of land‐use change on food chain length in tropical forest streams of Southeast Asia. Despite species losses associated with forest loss at our study areas, results from amino acid isotope analyses showed that food chain length was not linked to land use, ecosystem size or resource availability. Correspondingly, species losses did not have a significant effect on occurrence likelihoods of all trophic guilds except herbivores. Impacts of species losses were likely buffered by initial high levels of trophic redundancy, which declined with canopy cover. Declines in trophic redundancy were most drastic amongst invertivorous fishes. Declines in redundancy across trophic guilds were also more pronounced in wider and more resource‐rich streams. While our study found limited evidence for immediate land‐use impacts on stream food chains, the potential loss of trophic redundancy in the longer term implies increasing vulnerability of streams to future perturbations, as long as land conversion continues unabated. Abstract : Tropical forest streams are threatened by land‐use change. Despite this, this study finds no evidence linking food chain lengths to the loss of canopy cover. This is likely because initial high levels of species richness provide food web redundancy that can buffer against impacts of land use‐driven species loss.